Fernan Gonçalves de Seabra. Cantigas: Edizione critica a cura di Mariagrazia Staffieri (Carte Romanze, 2024)
Fernan Gonçalvez de Seabra, Galician-Portuguese troubadour of Leonese origins, is the author of sixteen love songs, fifteen of which cantigas de amor and one cantiga de amigo. Refined poet of typical love poetry of the Galician-Portuguese troubadour school, Seabra places the unstoppable force of an extremely distressing and painful love at the center of his poetic corpus. His cantigas, in fact, follow the traditional nuances of this genre and echo the most common topoi, without giving up on partial innovative impulses. Therefore, it is possible to appreciate a subtle rhetorical and technical elegance, quite remarkable in the tendency towards textual homogeneity and in the accurate experiments offered by the troubadour, who shows an original taste for thematic variation, as well as for continuous interior monologues.The monographic edition that is offered here aims to return the texts of the troubadour through a sure philological methodology of Lachmannian mold, as well as to provide an accurate historical-literary and linguistic characterization of the poet, through the substantial introductory study, which also implies an in-depth examination of the manuscript tradition, aimed at explaining any gaps and problems associated with the transmission of the texts.
Keywords: Fernan Gonçalvez de Seabra; Galician-Portugues Medieval Poetry; cantigas de amor; cantigas de amigo; critical edition